2021
DOI: 10.26434/chemrxiv.13171634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Dynamic Substrate is Required for MhuD-catalyzed Degradation of Heme to Mycobilin

Abstract: The non-canoncial haem oxygenase MhuD from <i>Mycobacterium tuberculosis</i> binds a haem substrate that adopts a dynamic equilibrium between planar and out-of-plane ruffled conformations. MhuD degrades this substrate to an unusual mycobilin product via successive monooxygenation and dioxygenation reactions. This article establishes a causal relationship between haem substrate dynamics and MhuD-catalysed haem degradation resulting in a revised enzymatic mechanism. UV/Vis absorption (Abs) and electr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 37 publications
(84 reference statements)
2
7
0
Order By: Relevance
“…The crude products of the ascorbate assay were analyzed by electrospray ionization mass spectrometry (ESI-MS) and the data (Figure S13) revealed that the major product of diheme MhuD catalysis is also mycobilin with m/z 611.25, like that of monoheme. A minor product with m/z 583.25 was detected at nearly identical relative abundance as previously reported data for the monoheme MhuD reaction, and was identified as biliverdin (37). Therefore, the products of heme degradation by diheme MhuD are highly consistent with that of monoheme in that its major products are mycobilins.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 79%
See 1 more Smart Citation
“…The crude products of the ascorbate assay were analyzed by electrospray ionization mass spectrometry (ESI-MS) and the data (Figure S13) revealed that the major product of diheme MhuD catalysis is also mycobilin with m/z 611.25, like that of monoheme. A minor product with m/z 583.25 was detected at nearly identical relative abundance as previously reported data for the monoheme MhuD reaction, and was identified as biliverdin (37). Therefore, the products of heme degradation by diheme MhuD are highly consistent with that of monoheme in that its major products are mycobilins.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 79%
“…While it is well-established that monoheme MhuD degrades heme to mycobilin products (3,17,37), the enzymatic activity of diheme MhuD reported here for the first time calls for characterization of its heme degradation products. The crude products of the ascorbate assay were analyzed by electrospray ionization mass spectrometry (ESI-MS) and the data (Figure S13) revealed that the major product of diheme MhuD catalysis is also mycobilin with m/z 611.25, like that of monoheme.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 79%
“…This heme structural change would be expected to change the ground state electronic configuration from 2 B2g to 2 Eg by decreasing mixing of the Fe 3dxy and porphyrin a2u orbitals (bottom) resulting in altered heme oxygenation activity. 5,13 Perhaps not surprisingly, the unusual geometric and electronic structures of the heme substrate in non-canonical heme oxygenases have often been invoked to explain the novel mechanisms of these enzymes. Prior to the characterizations of the geometric and electronic structures of S. aureus IsdG and IsdI described above, it was discovered that these enzymes degrade heme to novel staphylobilin products that are distinct from the biliverdin products of canonical heme oxygenases.…”
mentioning
confidence: 99%
“…19 Recently, it has been reported that both the R26S and W66F second-sphere substitutions can change the primary MhuD product from mycobilin to biliverdin. 13,20 These observations have been attributed to a mechanism where the structural and electronic dynamics of hemebound MhuD are critical: MhuD converts "ruffled" heme to meso-hydroxyheme and "planar" meso-hydroxyheme to mycobilin. The proposed monooxygenation mechanism is consistent with a recent QM/MM study of MhuD-catalyzed heme degradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation